2014
DOI: 10.1080/01932691.2013.833481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Weight on Mild Steel Corrosion Inhibition Effect by Polyvinyl Alcohol in Hydrochloric Acid Solution

Abstract: GRAPHICAL ABSTRACTThe corrosion inhibition of mild steel in hydrochloric acid solution in the presence of three different molecular weights of polyvinyl alcohol (PVA) designated as PVA-I, PVA-II, and PVA-III corresponding to 14,000, 72,000, and 125,000 g mol À1 , respectively, was investigated using electrochemical impedance spectroscopy, linear polarization resistance (LPR), and potentiodynamic polarization techniques at 25 C. It was found that PVA of different molecular weights inhibited the corrosion of mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 33 publications
0
3
2
Order By: Relevance
“…The inhibiting ability of dextran declined as the molecular weight increases such that Dex 2 and Dex 3 increased the metal charge transfer resistance to 179.400 Ω cm –2 and 165.200 Ω cm –2 respectively with 41.918% and 36.925% being the inhibition efficiency. This finding is contrary to the reports of Umoren and Gasem, Abdallah et al, and Finsgar et al that the inhibition efficiency of poly­(vinyl alcohol), polyethylene glycol, and polyethylenimine increased with increasing molecular weight but agreed with the submissions of Wang et al on carboxymethyl starch. Obviously, high molecular weight organic inhibitor should possess higher inhibiting property than low molecular weight counterpart since it should cover greater surface area.…”
Section: Resultscontrasting
confidence: 92%
“…The inhibiting ability of dextran declined as the molecular weight increases such that Dex 2 and Dex 3 increased the metal charge transfer resistance to 179.400 Ω cm –2 and 165.200 Ω cm –2 respectively with 41.918% and 36.925% being the inhibition efficiency. This finding is contrary to the reports of Umoren and Gasem, Abdallah et al, and Finsgar et al that the inhibition efficiency of poly­(vinyl alcohol), polyethylene glycol, and polyethylenimine increased with increasing molecular weight but agreed with the submissions of Wang et al on carboxymethyl starch. Obviously, high molecular weight organic inhibitor should possess higher inhibiting property than low molecular weight counterpart since it should cover greater surface area.…”
Section: Resultscontrasting
confidence: 92%
“…PDP and EIS measurements clearly showed that Cl-5c exhibits better inhibitive properties at 15 ppm and 298 K for 2 h (the IE values of Cl-5c and Cl-10c were 99.1% and 97.1%, respectively). This conclusion is not consistent with most of the published research (that is, the inhibition efficiency increases with increasing molecular weight) [ 233 , 234 ], while the explanation given by the authors was the higher degree of photo-cross-linking of the resultant Cl-5 polymer. Moreover, the two photo-cross-linked polymers at low concentrations exhibited good corrosion inhibition efficiency (>90% IE at 5 ppm).…”
Section: Classification and Statistical Analysiscontrasting
confidence: 73%
“…The corrosion inhibition of mild steel in hydrochloric acid solution containing three different molecular weights of polyvinyl alcohol (PVA) designated PVA-I, PVA-II, and PVA-III corresponding to 14,000, 72,000, and 125,000 g/mol respectively have been investigated using electrochemical impedance spectroscopy (EIS), linear polarization resistance (LPR), and potentiodynamic polarization (PDP) techniques at 25 o C [40]. It was found that the different molecular weights of PVA inhibit the corrosion of mild steel in HCl environment and the extent of inhibition was dependent on concentration and molecular weight of the polymer.…”
Section: Synthetic Polymers As Corrosion Inhibitors Of Mild Steelmentioning
confidence: 99%